Active-site properties of Phrixotrix railroad worm green and red bioluminescence-eliciting luciferases - Viviani, V. R.; Arnoldi, F. G. C.; Venkatesh, B.; Neto, A. J. S.; Ogawa, F. G. T.; Oehlmeyer, A. T. L.; Ohmiya, Y. (Japanese Biochemical Soc, 2006)
The luciferases of the railroad worm Phrixotrix (Coleoptera: Phengodidae) are the only beetle luciferases that naturally produce true red bioluminescence. Previously, we cloned the green- (PxGR) and red-emitting (PxRE) luciferases of railroad worms Phrixotrix viviani and P. hirtus[OLE1]. These luciferases were expressed and purified, and their active-site properties were determined. The red-emitting PxRE luciferase displays flash-like kinetics, whereas PxGR luciferase displays slow-type kinetics. The substrate affinities and catalytic efficiency of PxRE luciferase are also higher than those of PxGR luciferase. Fluorescence studies with 8-anilino-1-naphthalene sulfonic acid and 6-p-toluidino-2-naphthalene sulfonic acid showed that the PxRE luciferase luciferin-binding site is more polar than that of PxGR luciferase, and it is sensitive to guanidine. Alutagenesis and modelling studies suggest that several invariant residues in the putative luciferin-binding site of PxRE luciferase cannot interact with excited oxyluciferin. These results suggest that one portion of the luciferin-binding site of the red-emitting luciferase is tighter than that of PxGR luciferase, whereas the other portion could be more open and polar.
Keywords: bioluminescence; luciferases; Phrixotrix; railroad worms